Molecular phylogeny of the diatom genus Planothidium with the description of Paraplanothidium gen. nov. and Pseudoplanothidium gen. nov. - Natalia Tseplik; Yevhen Maltsev; Anton Glushchenko; Sergei Genkal; Maxim Kulikovskiy (PLoS ONE, 2025)
One of the characteristic features of the monoraphid genus Planothidium is the structure of the central part of the rapheless valve. Planothidium is divided into three groups based on this feature: with a sinus, a cavum, or with uninterrupted striae. Representatives of all three groups of Planothidium from the Kamchatka Peninsula have been studied using molecular (genetic markers 18S rDNA and rbc L) and morphological approach. Two new genera are separated from Planothidium : Paraplanothidium gen. nov., characterised by a cavum, and Pseudoplanothidium gen. nov., characterised by the absence of a horseshoe-shaped depression on the rapheless valve; this decision is supported by molecular data. Three new species from the new genera are described based on light and scanning electron microscopy as well as molecular analysis: Paraplanothidium laevis , Pseudoplanothidium foliiformis and Pseudoplanothidium minutum . New taxonomic combinations are proposed for previously described Planothidium species. This study contributes to the research of monoraphid diatoms taxonomy.